2018
DOI: 10.1002/joc.5398
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic circulation indices: links with summer and winter UK temperature and precipitation and implications for seasonal forecasting

Abstract: UK seasonal mean temperature and precipitation conditions are extremely variable from one year to the next but in the last decade have featured several cool, wet summers and mild, wet winters interspersed with some notable cold winter episodes. Jet stream variability is a major determinant of these fluctuations and is often represented by the North Atlantic Oscillation (NAO) index. Recent work has shown some evidence of promising predictability in the winter NAO from 1 to 2 months ahead, while summer predictab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
88
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 76 publications
15
88
0
Order By: Relevance
“…Our findings generally support the Woollings et al (2008) hypothesis that negative NAO arises from Greenland blocking and that positive NAO mainly represents the absence of blocking (rather than "anti-blocking" or negative GBI conditions). This is also in agreement with the results of Davini et al (2012b), who found that the first empirical orthogonal function of the 500 hPa geopotential height over Europe and the North Atlantic did not resemble the NAO for GBI cases but more closely resembled an East Atlantic circulation pattern (e.g., Hall et al, 2015;Hall and Hanna, 2018) and that North Atlantic jet variability was then no longer related to Greenland blocking changes. Also in support of our findings that high-GBI and low-NAO events do not always align, Rimbu et al (2017) found that stableisotope variations in GrIS cores are more closely related to measures of Atlantic-European/Greenland blocking than the NAO index.…”
Section: Discussion/summarysupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings generally support the Woollings et al (2008) hypothesis that negative NAO arises from Greenland blocking and that positive NAO mainly represents the absence of blocking (rather than "anti-blocking" or negative GBI conditions). This is also in agreement with the results of Davini et al (2012b), who found that the first empirical orthogonal function of the 500 hPa geopotential height over Europe and the North Atlantic did not resemble the NAO for GBI cases but more closely resembled an East Atlantic circulation pattern (e.g., Hall et al, 2015;Hall and Hanna, 2018) and that North Atlantic jet variability was then no longer related to Greenland blocking changes. Also in support of our findings that high-GBI and low-NAO events do not always align, Rimbu et al (2017) found that stableisotope variations in GrIS cores are more closely related to measures of Atlantic-European/Greenland blocking than the NAO index.…”
Section: Discussion/summarysupporting
confidence: 91%
“…This is also in agreement with the results of Davini et al . (), who found that the first empirical orthogonal function of the 500 hPa geopotential height over Europe and the North Atlantic did not resemble the NAO for GBI cases but more closely resembled an East Atlantic circulation pattern (e.g., Hall et al, ; Hall and Hanna, ) and that North Atlantic jet variability was then no longer related to Greenland blocking changes. Also in support of our findings that high‐GBI and low‐NAO events do not always align, Rimbu et al .…”
Section: Discussion/summarymentioning
confidence: 97%
See 1 more Smart Citation
“…Smith et al () and Hall et al () identified, besides North Atlantic SST, several drivers of NAO variability that enable predictability, among them, stratospheric variability, sea ice concentration, snow cover, solar variability, and El Niño. In northern Europe, the NAO is a major determinant of the air temperature (Hall & Hanna, ). Yet Hall and Hanna () concluded in their study the limited value of the NAO for the predictability of UK winter temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In northern Europe, the NAO is a major determinant of the air temperature (Hall & Hanna, 2018). Yet Hall and Hanna (2018) concluded in their study the limited value of the NAO for the predictability of UK winter temperatures.…”
Section: Introductionmentioning
confidence: 99%